Traditional Zapin Dance at Studio Tengku Buang Asmara Student, Siak District - Fitri, Aulia Annisa; Efi, Agusti (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
Zapin art in the Siak district was originally brought by Arab traders and used as a means of entertainment among students of recitation in the Siak royal environment, after the son of the sultan Abdul Jalil Alamuddin Syah (1766-1780) married Syarif Uthman bin Syarif Abdul Rahman Syahbuddin namely the Arabs then entered the palace environment and then acculturated with the local culture and became a means of entertainment among the palace then grew rapidly to the villages and Zapin associations were formed based on the names of the villages. Traditional Zapin dance is a dance movement that is more visible in footwork and more subtle in hand movements. Sanggar Tengku Buang Asmara is a place for artistic creativity that plays an important role in efforts to preserve the traditional Zapin dance. Zapin Dance Tradition during the sultanate period had rules and various flowers that must be followed and danced by the dancers. The purpose of this study is to understand the background, the form of presentation and to analyze the characteristics of the traditional Zapin dance in Siak district. This research was conducted in order to study, understand and preserve the Zapin dance tradition of the Siak kingdom. This qualitative research uses a descriptive analytical method, with a discussion of the historical background of the early arrival of Zapin art in the Siak kingdom. The Zapin dance tradition during the imperial era was only danced by 2 (two) male dancers whose position as the two dancers were parallel to the syaf and accompanied by Malay song music.